Do we need more research on the environmental impacts of plastics?. (1st September 2022) - Ryan, Peter G; Chitaka, Takunda Y
Abstract: We question whether the rapid growth in research on the impacts of environmental plastics over the last decade has substantially improved our understanding of these impacts. By the mid-1990s, the major environmental and economic impacts of plastics were sufficiently well known to conclude that they posed a significant environmental threat. Accordingly, the focus of the Third International Marine Debris Conference shifted from researching impacts to devising solutions. We should re-embrace this message, and study how best to change the inappropriate human behaviours that lie at the heart of the plastics crisis. The main role of natural scientists should be to provide robust monitoring data to assess the success of the various mitigation efforts.